Clinical Impact of Helicobacter pylori Infection on Gastric Ulcer Severity and Symptom Burden: A Cross-Sectional Study - Waheeda Baloch, Shakil Ahmad, Razwan Ashraf, Sheema Khan, Jawad Hameed, Asma Arshad Khan (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Gastric ulcer disease remains a significant cause of morbidity worldwide, particularly in regions where Helicobacter pylori infection is highly prevalent. The bacterium plays a central role in mucosal inflammation, ulcer formation, and progression to severe complications. Understanding how H. pylori influences ulcer severity and symptom burden is essential for optimizing diagnosis and clinical management. Objective: To assess the clinical impact of H. pylori infection on the severity of gastric ulcers and the associated symptom burden among adults presenting with dyspepsia. Methods: A cross-sectional study was conducted from June 2022 to July 2023 in the Medicine Department of Shaheed Mohtarma Benazir Bhutto General Hospital, Quetta, and Aziz Bhatti Shaheed Teaching Hospital, Gujrat, Pakistan. A total of 100 patients with endoscopically confirmed gastric ulcers were enrolled. H. pylori infection was identified using rapid urease testing, with histopathological confirmation in equivocal cases. Ulcer severity was classified using the Endoscopic Ulcer Severity Scale, and symptom burden was assessed through structured clinical evaluation. Statistical analyses were performed using SPSS version 26. Results: Of the 100 patients, 64% were H. pylori positive. Severe ulcers were significantly more common among infected individuals (46.9%) compared with non-infected patients (19.4%) (p = 0.003). H. pylori-positive patients also exhibited a higher symptom burden, including intense epigastric pain, nocturnal pain, nausea, vomiting, early satiety, and upper gastrointestinal bleeding (all p < 0.05). The findings indicate a strong association between H. pylori infection and both advanced ulcer severity and worsened clinical presentation. Conclusion: H. pylori infection is strongly associated with more severe gastric ulceration and a substantially higher symptom burden. Early diagnosis and prompt eradication therapy are critical for preventing complications, reducing symptom intensity, and improving overall patient outcomes in high-prevalence regions. Keywords: Helicobacter pylori; gastric ulcer; ulcer severity; dyspepsia; gastrointestinal symptoms; symptom burden.